A meta-network-based risk evaluation and control method for industrialized building construction projects. (20th December 2018) - Wang, Tao; Gao, Shangde; Li, Xiaodong; Ning, Xin
Abstract: Construction methods in developing countries such as China are gradually industrializing due to rising labor costs, new techniques, tools, procedures and management methods. This makes it essential to develop new risk evaluation and control methods. Previous research seems to ignore the risk management of the application of new construction technologies and procedures. The identification of risk mechanisms is unclear, leading to a lack of clear guidance for risk avoidance and control. This paper describes a network model based on meta-network analysis of project objectives, risk events, risk factors and stakeholders in the construction process of building industrialization. According to ISO 31000, the main processes of risk management in the model has three parts: risk identification, risk analysis and evaluation, and risk treatment and control. Risk factors are identified from previous literature and site investigation, and the indirect impact on project objectives is analyzed and calculated with the networks in the meta-network. The order of importance is evaluated and used as the foundation of risk treatment and control. The analysis of the crucial risk factors makes it possible to identify the stakeholders who influence them, leading to suggestions for relevant control strategies. A residential building construction project in South China that uses the building industrialization construction system serves as a case study to verify the feasibility and applicability of the risk management system. Results show that critical risk factors are construction-related factors and design-related factors. The water and electricity engineers, the project manager, the project secretary, the field engineer, the project supervisor and the main contractor engineer have a significant influence on the risk factors. A stakeholder supervision system with targeted risk control strategies is proposed.